농촌지역 공공보건시설의 공간적 형평성 및 입지 효율성 분석 - 김_현중 (한국농촌경제연구원, 2011)
Public healthcare services ought to be evenhandedly provided or accessible to any citizen. However, rural areas, having large elderly population that is traditionally vulnerable and underserved with respect to healthcare, are in the lack of healthcare infrastructures, comparing to those of urban areas. The main purpose of this paper is to investigate the level of spatial equity of public healthcare facilities for rural areas in Korea. This study analyzes the spatial equity and locational efficiency of public healthcare facilities in 80 rural areas. To evaluate the spatial equity, population of each administrative unit is transformed to a grid map using dasymetric mapping method. Service areas and population are extracted to evaluate the spatial equity, and then the locational efficiency is evaluated using the number of residents within the serviceable areas. Results showed that the whole public healthcare facilities help 91.2% of rural population and average geographic boundary of each facility covers 106.7 persons per 1km2. We also found that deviations in the locational efficiency were as much wide as they are in the spatial equity. Rural areas in Chungcheongnam-do rated the highest in the spatial equity and the locational efficiency, while rural areas in Gangwon-do rated the lowest. This study concludes with suggesting some policy issues that need to be considered in the provision of public healthcare facilities in rural areas.
Keywords: 공공보건시설; 공간적 형평성; 공간적 접근성; 입지 효율성; 에어리얼 인터폴레이션; public healthcare facility; spatial equity; spatial accessibility; locational efficiency; areal interpolation